Ustad Strategy in Moral Development in the Sea Tribe Communities on Kojong Island: Strategi Ustad dalam Pembinaan Akhlak pada Masyarakat Suku Laut di Pulau Kojong - Nazaruddin, Nazaruddin; Zaimah, Zaimah (Journal of Educational Review and Cultural Studies, 2023)
Moral are important in life, in the world and hereafter. Good morals have impacton good life and vice versa. Thus, knowledge abaout morals and moral developmet is very necessary. This is no exception for the Sea Tribe community. Purpose of the research is find out the strategies of the master in moral development and factors that influence it. So, this research is include in qualitative research. Obtaining data used observation, interviews, and documentation. Analyzing using John Creswell Data Analysis. And the result is master used strategy in moral development of local curriculum, and emotional approach. The supporting factors were motivation, enthusiasm, and open attitude. The inhibiting factors is lack of human resources and infrastructure.